Impact of psoriasis disease severity and special area involvement on patient-reported outcomes in the real world: an analysis from the CorEvitas psoriasis registry - Bruce Strober; Kristina Callis Duffin; Mark Lebwohl; Adam Sima; Jud Janak; Manish Patel; Huzefa Photowala; Vishvas Garg; Jerry Bagel (Journal of Dermatological Treatment, 2024)
Background The impact of psoriasis in special areas (i.e., scalp, nails, palms, soles, genitals) on patient physical functioning, health-related quality of life (HRQoL), and work abilities has not been fully characterized. We assessed associations between disease severity and special area involvement in psoriasis symptoms, HRQoL, and work/activity impairment.Methods Patients with psoriasis from the CorEvitas Psoriasis Registry who initiated systemic treatment between 04/2015–06/2020 were included. Outcomes were change from baseline in psoriasis symptoms, Dermatology Life Quality Index (DLQI), and work/activity impairment at 6 months stratified by baseline disease severity and special area involvement.Results Among 2620 patients, increasing disease severity was associated with worsening patient-reported outcomes. Patients with (46.0%; N = 1205) versus without (54.0%; N = 1415) psoriasis in special areas reported greater HRQoL and work/activity impairment. Over 6 months, patients with unchanged or worsening disease severity had reduced HRQoL and increased symptom severity; incremental increases in patient HRQoL and decreases in symptom severity were associated with improved disease severity.Conclusions Higher disease severity and special area involvement was associated with worse outcomes and impaired work abilities. These data highlight the significant impact that adequate treatment of severe psoriasis and/or special area involvement may have on patient HRQoL and function.